Genetically Modified Mice as Tools to Understand the Neurobiological Substrates of Depression - Robledo, Patricia; Martín-Garcia, Elena; Aso, Ester; Maldonado, Rafael (Current Pharmaceutical Design, 2014)
The pathophysiological mechanisms underlying depression are still poorly understood. An initial hypothesis postulated to explain the substrates of depression was based on the involvement of monoaminergic systems. This early theory was proposed from different findings obtained using pharmacological tools and can explain the mechanism of action of the drugs currently used to treat depression. However, more recent studies have revealed that other neurobiological processes different from monoamines also participate in the substrates of depression. These mechanisms include the participation of several neuromodulatory systems, stress-related circuits and neuroplastic changes that could represent a direct substrate for these pathophysiological processes. The lack of selective pharmacological tools for several of these potential targets of depression represents an important limitation to study their potential involvement. In the last two decades, different lines of genetically modified mice have been generated with selective deletions in specific genes related to the control of emotional responses. This review summarizes the main findings that have been obtained with these novel genetic tools to clarify the neurobiological substrates of depression. A particular focus has been devoted to the advances obtained with mice deficient in specific components of the monoaminergic, opioid and cannabinoid system and those with mutations in elements of the hypothalamic-pituitaryadrenal axis.
Keywords: mood disorders